2018
DOI: 10.1016/j.ijrobp.2018.01.001
|View full text |Cite|
|
Sign up to set email alerts
|

Phase 2 Study of Bortezomib Combined With Temozolomide and Regional Radiation Therapy for Upfront Treatment of Patients With Newly Diagnosed Glioblastoma Multiforme: Safety and Efficacy Assessment

Abstract: Purpose/Objective: To assess the safety and efficacy of upfront treatment using bortezomib in combination with standard radiation therapy (RT) and temozolomide, followed by adjuvant bortezomib and temozolomide for up to 24 cycles in patients with newly-diagnosed glioblastoma multiforme (GBM). Patients and Methods: Twenty-four newly-diagnosed GBM patients were enrolled. Patients received standard external beam regional RT with concurrent temozolomide commencing 3–6 weeks after surgery, followed by adjuvant te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 19 publications
2
41
0
1
Order By: Relevance
“…Even in this setting, the survival is still limited at a median of 20.9 months (4). Given these poor outcomes, there is hope that up-and-coming therapies will show benefit in the randomized setting (5, 6). It will be essential to ascertain which patients can benefit from these therapies, highlighting the need for efficacious tools to offer personalized medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Even in this setting, the survival is still limited at a median of 20.9 months (4). Given these poor outcomes, there is hope that up-and-coming therapies will show benefit in the randomized setting (5, 6). It will be essential to ascertain which patients can benefit from these therapies, highlighting the need for efficacious tools to offer personalized medicine.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Several clinical studies investigated BTZ as an add-on therapy to low doses of TMZ 17 combined with radiotherapy, 18 bevacizumab, 17 Tamoxifen 19 or HDAC inhibitors, 20 or as monotherapy 21 and all deemed it safe and tolerated. 19,21,22 A recent phase II study reported some survival benefit 23 after prolonged treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with previous trials using concurrent schedules 22 with intensive and prolonged treatment, as well as with various drug combinations. [33][34][35][36][37][38][39] Our patients scored relatively high on the quality of life EQ-5D-5L questionnaire that was previously validated for the Norwegian population. 40 The ability to perform usual daily activity, ataxia, and changes in strength were the strongest predictors of KPS and this finding is corroborated by a previous study of Norwegian patients after surgery.…”
Section: Discussionmentioning
confidence: 83%
“…BTZ, bortezomib; IFNγ, interferon γ; IL, interleukin; TMZ, temozolomide; TNF-α, tumor necrosis factor α schedule with monotherapy BTZ, metronomic doses of TMZ, or were conducted in newly diagnosed patients. [33][34][35][36][37] In this phase IB study, we successfully dose escalated TMZ to the target 200 mg/m 2 dose for combination with 1.3 mg/m 2 BTZ and no grade 3 or 4 toxicities were registered in our study. This is consistent with previous trials using concurrent schedules 22 with intensive and prolonged treatment, as well as with various drug combinations.…”
Section: Discussionmentioning
confidence: 90%